Extrapulmonary manifestations of SARS-CoV-2 in a tertiary care centre in South India - B., Sashidhar Reddy; Alekhya; Pentachary; Jain, Archana; Tadikonda, Daiwik (International Journal of Research in Medical Sciences, 2024)
Background: COVID-19 is primarily a respiratory disease caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). However, extrapulmonary manifestations were also quite frequently seen among the patients. Aims and objective of the study was to assess the extrapulmonary manifestations of COVID-19 in a selected group of patients. Methods: The study was conducted at RVM Hospital, Siddipet on patients aged between 18-99 years, confirming to the World Health Organization (WHO) criteria for COVID-19. A total of 307 patients have been taken into consideration for this study. Results: Cardiovascular, neurological, gastrointestinal (GIT) were the most common extrapulmonary systems being affected apart from hematological and endocrine systems. Coronary artery disease (67%) was the most common cardiac abnormality noted and ischemic stroke (86%) was the most common neurological problem. Type 1 DM, diarrhoea, conjunctivitis, hypothyroidism were the other diseases frequently encountered. Conclusions: COVID-19, whilst being primarily a respiratory disease, can also affect the various systems in the body. Having said that, the most common extrapulmonary manifestations noted were cerebrovascular accidents (CVAs), myocardial infarctions (MI), pancreatitis and diarrhea.